2022
DOI: 10.3390/cancers14092079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraductal RFA Plus Stent versus Stent-Only Treatment for Unresectable Perihilar Cholangiocarcinoma—A Systematic Review and Meta-Analysis

Abstract: Background: One of the cornerstones of palliative treatment for unresectable perihilar cholangiocarcinoma is biliary stent placement in order to restore biliary drainage. In this review, the potential added value of RFA with stent placement in comparison to stent placement alone in patients with unresectable perihilar cholangiocarcinoma is analyzed. Methods: We performed a comprehensive online search for relevant articles in November 2021 (PROSPERO ID: CRD42021288180). The primary endpoint was difference in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…A recent meta-analysis that included 19 studies (3 RCT and 16 OS) suggests that RFA is associated with the improved survival and stent patency time of patients with MBO. 36 Another meta-analysis conducted by de Jong et al, 37 which included 9 articles and included a total of 511 patients with unresectable perihilar CCA, found that RFA treatment showed promising outcomes to improve patients' survival times. In their study, Song et al 38 showed the results of a Bayesian network meta-analysis of 33 trials with a total of 2974 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis that included 19 studies (3 RCT and 16 OS) suggests that RFA is associated with the improved survival and stent patency time of patients with MBO. 36 Another meta-analysis conducted by de Jong et al, 37 which included 9 articles and included a total of 511 patients with unresectable perihilar CCA, found that RFA treatment showed promising outcomes to improve patients' survival times. In their study, Song et al 38 showed the results of a Bayesian network meta-analysis of 33 trials with a total of 2974 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that patients who received intraductal RFA had prolonged average OS (19 months vs 16 months, P = 0.04), improved quality of life, and more significantly improved liver and kidney functions 31 . Recent meta‐analyses have also suggested that compared to stenting alone, endobiliary RFA combined with stent implantation can prolong patient survival and stent patency in MBS without increasing the incidence of adverse events 32–35 . These studies include MBS of various etiologies, most of which are inoperable extrahepatic cholangiocarcinoma, including hilar and distal cholangiocarcinoma.
Recommendation 1: Endoscopic RFA is recommended for palliative treatment of inoperable extrahepatic cholangiocarcinoma.
…”
Section: Indications For Endobiliary Rfamentioning
confidence: 99%
“…The incidences of complications in endobiliary RFA have been reported to range from 4.2% to 35%, including pancreatitis, cholangitis, cholecystitis, ampullary stenosis, and bleeding, 34,61 which are closely associated with the ERCP procedure, biliary drainage, tumor location, and the anatomical relationship with the adjacent organs. Several meta‐analyses have confirmed that RFA does not increase the additional risk of adverse events compared to conventional ERCP 32–35,61 . However, it may still lead to certain complications; therefore, sufficient attention should be paid to and active prevention and treatment should be taken for high‐risk patients.…”
Section: Prevention and Treatment Of Complications In Endobiliary Rfamentioning
confidence: 99%
“…In addition, there is a lack of information regarding the length and etiology of MBO. In an attempt to reduce the heterogeneity of the results, previous meta-analyses [2,3,4,5,6] included non-RCTs to increase the sample size. However, that measure does not increase the quality of evidence and should be evaluated with caution.…”
Section: Reply To Chandrasekhara and Aggarwalmentioning
confidence: 99%